PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SDN 003 BANGKINANG KOTA - Nelda Azriani; Neni Hermita; Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The research is based on the low learning outcomes of IPA students of grade III SDN 003 Bangkinang Kota. This is due to the the teacher’s central learning. For learning IPA the inquiry learning model is a suitable model to use. The inquiry model makes learning student centered so as to emphasize student activity to find out for themselves the answer to what is being questioned. This study aims to determine the imporvement of IPA learning outcomes of students by implementation use inquiry model. Method this research is Quasi Eksperiment Nonequivalent Grup Pretest-postest Design. This study was conduted on 54 subjects of primary school students’ in SDN 003 Bangkinang. The results this research was improving learning outcomes students after implementation inquiry model. Based on the results of research obtained learning outcomes of IPA students who learn with inquiry learning model better and higher than on learning with conventional model. Seen from the value of the gain index in the experimental class of 0,52 which is the medium category, while the value of gain index in conventional class is 0,19 which is low kategory. This suggest that the inquiry model can improve the learning outcomes of IPA on the Primary School Students.Keyword: Inquiry model, learning outcomes of IPA